A mixed-integer model for the implementation of postponement strategies in the globalized green supply chain network. (November 2019) - Budiman, Syarif Daniel; Rau, Hsin
Highlights: Green supply chain network models considering postponement strategies are proposed. Modular products and processes are considered to model mass customization process. The effects of carbon tax and carbon cap on supply chain operations are analyzed. Numerical examples of notebook computer global supply chain are investigated. Postponement strategies could reduce costs even in strict environmental policies. Abstract: Modern business traits and global-scale logistics operations have urged companies to devise responsive and efficient supply chain networks to fulfill customer demands all- around the world. However, such operations have increased resource consumption and pollution production, causing more environmental damage. To address these issues, postponement strategies are adopted to enable responsive and more environmentally friendly supply chain operations. However, only a few studies on supply chain optimization considering postponement strategies and environmental issues have been conducted. It motivates this study to propose a mixed-integer model of an integrated green supply chain network (GSCN) for both single and multi-period planning horizons that incorporate postponement concept, and modularized products and processes. Using these models, various speculation strategies coupled with postponement strategies can be analyzed in configuring green supply chain system with mass customization principle subjected to various carbon tax and carbon cap policies under a global supply chain environment. Computational examples of a mass customization notebook computer supply chain show that postponing product differentiation reduces excessive production processes. As a result, the configured supply chain is able to comply with strict environmental policies with just a slight cost increase. This justifies postponement strategies application in configuring eco-efficient supply chain operations.